2014
DOI: 10.7567/apex.7.096501
|View full text |Cite
|
Sign up to set email alerts
|

Improved breakdown voltage and RF characteristics in AlGaN/GaN high-electron-mobility transistors achieved by slant field plates

Abstract: We experimentally demonstrate the efficacy of using slant field plates (field plates with the plate-to-channel gap gradually increasing away from the gate edge) on the breakdown voltage. We develop a new fabrication process using a multi-step SiCN film such that both slant and conventional field plates are fabricated simultaneously. Consequently, we fabricate 230-nm-gate AlGaN/GaN HEMTs with several types of field plates. The slant field plate increases the breakdown voltage by 66% more than that of the conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The dry etching properties of the deposited film, such as etching rate, depend on these carrier gases. 13,14) As a result, the carrier gas profile affects the cross-sectional shape when the SiCN film is etched. This will be discussed in Sect.…”
Section: Fabrication Of Slant Fp Using Multi-step Sicnmentioning
confidence: 99%
See 1 more Smart Citation
“…The dry etching properties of the deposited film, such as etching rate, depend on these carrier gases. 13,14) As a result, the carrier gas profile affects the cross-sectional shape when the SiCN film is etched. This will be discussed in Sect.…”
Section: Fabrication Of Slant Fp Using Multi-step Sicnmentioning
confidence: 99%
“…Recently, we have developed slant FPs using multistep SiCN that enables us to perform a systematic experiment to prove the advantage of slant FPs over conventional FPs. 13,14) More recently, Corrion et al has been reported both a source-connected slant FP 15) and a gateconnected slant FP. 16) They also proved the advantage of slant FPs in terms of reduced dynamic on-state resistance and gate capacitance.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the technique of multiple field plates (FP) is adopted to manage the distribution of surface electric field in GaN HEMTs [2,3]. However, the processing of multiple FP is difficult [2][3][4] and FP structure will increase the parasitic capacitance, which results in the degradation of high-frequency performance of the device [5,6]. In addition, doping Fe/C in GaN buffer layer [7,8] is also one of the feasible solutions for breakdown enhancement.…”
mentioning
confidence: 99%
“…For GaNbased HEMTs, many research groups reported improvements in BV using FPs. [7][8][9][10][11][12][13][14] In particular, the use of a slant FP is reported as the most effective way of reducing the maximum electric field at the gate edge. [8][9][10][11][12][13][14] The advantage of the slant FP over the conventional FP was studied theoretically 9,10) and experimentally [11][12][13][14] For GaN-based HEMTs.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] In particular, the use of a slant FP is reported as the most effective way of reducing the maximum electric field at the gate edge. [8][9][10][11][12][13][14] The advantage of the slant FP over the conventional FP was studied theoretically 9,10) and experimentally [11][12][13][14] For GaN-based HEMTs. Kobayashi et al reported the fabrication of slant FPs using a multistep SiCN film and demonstrated for the first time increased BV in comparison with that using conventional FPs.…”
mentioning
confidence: 99%